EFEKTIFITAS PEMBELAJARAN BAHASA ARAB DARING PADA MASA PANDEMI COVID-19 DI FAKULTAS AGAMA ISLAM, UNIVERSITAS ISLAM MALANG - Muhammad Afifullah; Siti Masruchah (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
During this Covid-19 pandemic, the learning process at the Faculty of Islamic Science, University of Islam Malang, including Arabic language courses cannot be done directly (face to face) in order to avoid massive transmission of the virus, but must be done online (in a network). using various internet applications. The purpose of this study was to photograph the effectiveness of learning Arabic online. The method of data collection in this study was conducted through question and answer and interviews with the resource persons, namely lecturers and students as well as observation. The results of this study indicate that the Arabic language learning process at the Faculty of Islamic Religion, Islamic University of Malang is quite effective, although there are some shortcomings related to technical mastery of application operations, expensive data quotas and also difficult class control, so a more innovative learning model is needed. so that the lessons given can be understood properly.